2016
DOI: 10.4238/gmr.15028223
|View full text |Cite
|
Sign up to set email alerts
|

Association between transcription factor 7-like 2 genetic polymorphisms and development of type 2 diabetes in a Chinese population

Abstract: ABSTRACT. We conducted a hospital-based case-control study to evaluate the relationship between the transcription factor 7-like 2 (TCF7L2) rs7903146 polymorphism and type 2 diabetes mellitus risk in a Chinese population. Genotyping of TCF7L2 rs7903146 was carried out using the polymerase chain reaction-restriction fragment length polymorphism method. A chi-square test revealed a statistically significant difference between the distributions of rs7903146 genotypes in type 2 diabetes mellitus patient and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Beyond the ethnic influence that has also been found in other studies of rs12255372 and rs7903146[ 17 - 25 ], this study showed that the association of rs12255372 with diabetes was increased when the population was reclassified as subgroups of case types and only the classical T2D patients were compared with controls. This finding suggests the importance of taking into consideration the existence of an atypical group, which could serve to obscure the real association of SNPs in the TCF7L2 gene.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Beyond the ethnic influence that has also been found in other studies of rs12255372 and rs7903146[ 17 - 25 ], this study showed that the association of rs12255372 with diabetes was increased when the population was reclassified as subgroups of case types and only the classical T2D patients were compared with controls. This finding suggests the importance of taking into consideration the existence of an atypical group, which could serve to obscure the real association of SNPs in the TCF7L2 gene.…”
Section: Discussionsupporting
confidence: 63%
“…Diabetes mellitus is a complex disease, in which genetic and environmental factors are interweaved. After the discovery of TCF7L2 as a key player in T2D etiology, several works in multiethnic populations identified two main SNPs in this gene, rs12255372 and rs7903146, and characterized them as the most relevantly associated to T2D[ 9 , 10 , 17 , 21 ]. In our previous works[ 3 - 5 ], we reclassified patients who are clinically diagnosed as T2D into two subgroups, representing the classical and atypical cases, as described in the Materials and Methods section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon might be due to impaired insulin secretor and/or insulinotropic effects of incretins rather than an insulin resistance [ 21 , 22 ]. Recently, several case-control studies focused on the relationship of TCF7L2 rs7903146 C>T with the development of T2DM in China [ 7 , 10 , 11 ]. The results of a meta-analysis also indicated that TCF7L2 rs7903146 C>T variants might confer an increased risk to T2DM in Chinese population [ 13 ].…”
Section: Discussionmentioning
confidence: 99%